Geometric modification of gable roof for low-rise buildings to reduce wind demand - Maliwanag, Julian Eymard B.; Hernandez, Jaime Y. Jr.; Tan, Liezl Raissa E. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Wind demand due to typhoons cause severe damages on houses especially nonstructural elements like the roof. The gable roof, being commonly used in residential construction, suffers high suction pressure due to these high speed winds. This research will look into new ways of modifying the gable roo[structure so as to reduce the wind demand and ultimately reduce wind suction or redirect wind action. In this research, Computational Fluid Dynamics will be used in the modeling and analysis of wind flow on the gable roof structure and modifications. Modifications like the Pagoda, Combined, Diamond, Ellipse, and Wind spoiler placed at the edge of the roof produced overall positive responses to the reduction of negative (suction) pressure and uplift forces on the roof.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Wind-pressure.; Roofs -- Aerodynamics